Utilization of geothermal energy in the Parrylands Field for electricity production / Khufrah Lessey... [et.al.] - Lessey, Khufrah; Alexander, David; Boodlal, Donnie; Rean, Maharaj (2023)
Trinidad and Tobago (TT) was ranked as the second-highest emitter of carbon dioxide per capita in 2020. Similar to other Small Island Developing States (SIDS), TT is vulnerable to the negative effects of climate change and is also a signatory to the Paris Agreement. The use of renewable energy especially Enhanced Geothermal Systems (EGS) is receiving much attention in many parts of the world today. Therefore, this study seeks to evaluate the possible use of EGS for electricity production by using abandoned oil and gas reservoirs in the Parrylands field located in southern TT. This study confirmed that abandoned oil and gas reservoirs in the Parrylands field in TT could utilize EGS for electricity production and CO2 emissions reduction. A simulation model was built using CMG and the model was used to quantify the optimal amount of energy that can be produced.